Financial statements under the economy globalization conditions: ways and perspectives of the development - Ronek, H.; Lemishovska, O. (Lviv Politechnic Publishing House, 2018)
The key issues are described of the current information field of the public financial statements of modern corporate companies in the context of its functions with regard to the information insurance of different users under the conditions of the global post-industrial economy. The assessment was conducted of the methodological aspects of accounting of separate objects of the modern corporations’ public accounting. The key aspects are provided of the negative impact of the restricted information of the financial statements of transnational and socially important national companies and the processes of management and regulation of the national and global economy. The suggested perspectives are analyzed in the theory and world business practice of the development of conceptual grounds for the solution of problem of the adaptation of the format of public statements system of the corporations to the modern economic conditions and informational needs of different groups of users, including the market institutional formations. The need was accentuated of the improvement of accounting approach and principles of presentation of the value of modern corporations’ capital. Certain aspects of the development of current basic financial statements fundamentals are justified and suggested.
Keywords: financial statements; system of indexes; theories; paradigms; adaptation; cost criteria; 657. 1; 658.041